Haven House : Adaptive reuse of the Old Poynton's Building as a mixed-use commuity centre for asylum seekers and refugees - Khan, Zakkiya (University of Pretoria, 2020)
Mini Dissertation (MInt (Prof))--University of Pretoria, 2019.